2010
DOI: 10.1111/j.1743-6109.2010.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Well-Being ScaleTM: Responsiveness to Interventional Product Use by Sexually Functional Women

Abstract: Introduction Initial psychometric evaluation of the Female Sexual Well-Being ScaleTM (FSWB ScaleTM) demonstrated its validity for assessing sexual well-being in sexually functional US women. Aim To evaluate the responsiveness of the FSWB Scale to interventional products in sexually functional women and to confirm its psychometric validity. Methods In a 5-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Overall, lubricant use was associated with higher sexual pleasure and satisfaction during both solo and partnered sex [4]. According to a Johnson & Johnson funded study, the use of personal lubricants increased sexual well‐being for healthy women [15].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, lubricant use was associated with higher sexual pleasure and satisfaction during both solo and partnered sex [4]. According to a Johnson & Johnson funded study, the use of personal lubricants increased sexual well‐being for healthy women [15].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model of sexual well-being represents a more comprehensive, global conceptualization of the positive aspects of a person's sexual life. According to the literature and our clinical experience, sexual well-being is a broader construct than personal sexual satisfaction and clearly distinct from it (Anderson 2013;Contreras et al 2016;Neto 2012;Rosen et al 2010;Rosen and Bachmann 2008). It also goes beyond narrow definitions of sexual health that focus on sexual functioning and the frequency of sexual activity (cf.…”
mentioning
confidence: 99%
“…Among women with dyspareunia, alleviating pain was the main reason women reported lubricant use; however, women in this sample rated lubricant use as only moderately effective in reducing pain during sex [5]. In assessing the psychometrics of the Female Sexual Well‐Being Scale, women reported higher scores on the orgasm‐satisfaction domain when using a lubricant [13]. Additionally, Herbenick and colleagues found that solo and partnered sexual activities that included lubricant use were associated with higher ratings of sexual pleasure and satisfaction compared to solo and partnered sexual activities during which no lubricant was used [14].…”
Section: Introductionmentioning
confidence: 74%